THE ROLE OF MOTHERS AS LEARNING COMPANIONS IN KURIKULUM MERDEKA: A Study Through Relational Dialectics Theory - Susanti, Asta Ayu; Prasetyo, Bambang Dwi (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
This study examines the evolving roles of mothers in facilitating their children's education within Indonesia's Kurikulum Merdeka.  This curriculum prioritizes student autonomy, personalized learning, and less reliance on strict instruction, hence raising the expectation for mothers to offer both academic assistance and emotional support at home.  The study employs a qualitative method rooted on a phenomenological paradigm, utilizing in-depth interviews with purposefully selected participants to explore how mothers navigate the tensions between autonomy and guidance.  The findings underscore their crucial responsibilities in promoting autonomous learning while managing dialectical challenges, such as the balance between control and freedom, as well as emotional intimacy and children's increasing independence. Additionally, technology has emerged as both a facilitator and an obstacle, transforming family communication and educational practices.  The research illustrates the cultural, emotional, and logistical difficulties put on mothers and proposes pragmatic solutions, such as digital literacy workshops, community-oriented support networks, and fair access to educational resources.  These findings aim to enhance the overarching theoretical discussion on relational dialectics and provide practical solutions to augment family involvement in education within changing educational environments.